The isolations of Toxoplasma gondii from diaphragm of a sheep having high antibody titre and faecal-soil of a cat - Iskandar, Tolibin (Indonesian Journal of Animal and Veterinary Sciences, 1998)
In relation to isolate Toxoplasma gondii from animals, 161 samples each of serums pairs and diaphragms were collected from 123 sheep and 38 goats from an abbatoir of Cibadak subdistrict, district of Sukabumi, and 30 faecal-soil samples of cats from some areas in district of Bogor. By using indirect haemagglutination (IHA) test serums were examined, and 60.16% and 39.47% of sheep and goats serums were found positive toxoplasmosis with antibody titres varied ranging from 1 :64 to 1 :8 .192 . Meanwhile, diaphragms of sheep and goats having antibody titres higher than 1 :2 .048 were extracted and the extracts were then passaged by innoculating into mice intraperitoneally . The results showed that cysts and tachyzoites of Toxoplasma were isolated from brain and peritoneal exudate ofmice respectively which were formerly innoculated by diaphragm extract of a sheep Â having the highest (1 :8 .192) antibody titre. On the other hand, oocysts of Toxoplasma were also isolated from one out of 30 (3.33%) faecal-soil samples ofcats examined by floatation method. Â  Key words : Toxoplasmosis, Toxoplasma gondii, sheep, cysts, tachyzoites, faecal-soil, oocysts